The impact of educational interventions on clinicians' knowledge of radiation protection: An integrative review. Issue 3 (August 2020) - Hankin, R.A.; Jones, S.P.
Abstract: Objectives: The aim of this review is to explore the impact of educational interventions on clinicians' knowledge of radiation protection. Key findings: Following a comprehensive search of MEDLINE and EMBASE from 2000 to 2018, 1795 studies were identified, eight of which met the criteria for this review. All eight studies utilised pretest-posttest designs and involved the education of medical students or doctors. All studies reported an increase in participants' knowledge of radiation protection, five of which were statistically significant. In two studies, over half of participants stated that education received would impact on their future imaging requesting practice. Conclusion: Whilst a range of educational interventions have been shown to improve knowledge of radiation protection, there was wide variation in the study settings and type of educational programmes delivered. No studies assessed long-term knowledge retention or the impact on clinical practice. Therefore, robust research is needed to accurately measure the impact of educational programmes on knowledge of radiation protection in the UK and the implications this may have on referral practices. Implications for practice: This review revealed that educational interventions are effective in increasing participants' knowledge levels of radiation protection. It is necessary to assess and ensure that this improvement in knowledge actually translates into an impact on referral practice/behaviour. The ideal outcome being that fewer unnecessary examinations are requested and our patients are protected from a needless increased radiation burden.